CFD modelling of flow and heat transfer within the parallel plate heat exchanger in standing wave thermoacoustic system. - Mohd Saat, Fatimah Al Zahrah; Yu, Zhibin; Jaworski, Artur (2012)
Thermoacoustics is a sustainable technology for novel energy conversion applications. The performance of future thermoacoustic systems can be improved through a better understand- ing of the complex fluid flow and heat transfer phenomena that form the fundamental basis for the system construction. Here, a particular attention is focused on heat exchangers. This paper investigates the flows and heat transfer within parallel plate heat exchangers working in a thermoacoustic environment characterised by an oscillatory flow induced by a standing wave. A two-dimensional computational fluid dynamics (CFD) model was developed and validated using earlier experimental data obtained within our group. The natural convection effect which is commonly neglected in most numerical analyses was included in this compu- tational investigation to account for temperature-driven buoyancy effects observed in exper- iment. The flow and heat transfer characteristics were investigated by obtaining the velocity and temperature profiles over twenty periods of a flow cycle. The velocity profile was found to be distorted due to the presence of temperature, indicating a change in the flow structure. Temperature profiles produced by the computational model agreed qualitatively with the ex- perimental model, but with differences in magnitude particularly noticeable in the area of the hot heat exchanger. Thus the temperature profile appears to have the same trend and pattern over the whole phases investigated, apart from the slight differences in the aforementioned area. Accordingly, the space average wall heat flux was discussed for different phases and lo- cations across both cold and hot heat exchanger. Discussion includes the effect of gravity and device orientation to the flow and heat transfer. The results thus contributed toward a better understanding of the hydrodynamic and thermal performance of the flow investigated and eventually it will assist in experimental design for future research.